The smile gap : a history of oral health and social inequality - Carstairs, Catherine, 1969- (McGill-Queen's/Associated Medical Services studies in the history of medicine, health, and society, 2022)
"As recently as fifty years ago most people expected to lose their teeth as they aged. Few children benefited from braces to straighten their teeth, and cosmetic procedures to change the appearance of our smiles were largely unknown. Today, many Canadians enjoy straight, white teeth and far more of them are keeping their teeth for the entirety of their lives. Yet these advances have not reached everyone. The Smile Gap examines the enormous improvements that have taken place over the past century. The use of fluorides, emphasis on toothbrushing, the rise of cosmetic dentistry, and better access to dental care has had a profound effect on the oral health and beauty of Canadians. Yet while the introduction of employer-provided dental insurance in the 1970s has allowed for regular visits to the dentist for many people, a significant number of Canadians still lack access to good oral health care, especially disabled Canadians, those on social assistance, the working poor, the elderly, and new immigrants. At the same time, an attractive smile has become increasingly important in the workplace and in relationships. People with damaged and missing teeth are at a substantial disadvantage, not just because of the pain and suffering caused by poor oral health, but because we live in a society that prizes good teeth and warm smiles. The first history of oral health in Canada, The Smile Gap reveals that despite the gains made, too many Canadians go without any dental care, with damaging consequences for their oral health, general physical health, and self-image. To complete our health care system, it is time to close the gap."--